Fresh and Hardened Properties of Steel Fiber-Reinforced Self-Consolidating Concrete - Maan S. Hassan; Iqpal N. Gorgis; Aymn H. Ali (Engineering and Technology Journal, 2015)
The main aim of this research is to study the effect of using hooked end steel fiber on the fresh and hardened properties of self-consolidating concrete. The experimental work includes two stages. First stage involved conducting several trial mixes and then choosing the one that conform tothe international standards in terms of fresh properties. Second stage concerned on the compressive, flexural tensile and splitting tensile strengths evaluationof the selected mixes, at 28 and 90 days.Four concrete mixes were obtained and evaluated. They were similar in mix proportions and differ only in volume fractions of steel fibers incorporated: 0%, 0.5%, 1%, and 1.5%. Results showed that adding hooked steel fibers adversely affect SCC workability and thus more dosage of SP should be added to stay within the standard limits. Similar to conventional HPC, the presence of steel fibers with SCC provide slight increase in compressive strength at 28 days, (up to 11%), while significant enhancement in tensile properties were observed (up to 68% and 80% for splitting and flexural strength respectively). Flexural strength (i.e. modulus of rapture) was generally still higher than splitting testing results in a decreasing order. This order is still applicable in SCC even with the presence of steel fibers.